Seasonal Variation in Nematode Infestation Across Bahar Treatments in Pomegranate Cultivation - Shivam Satyawan Madrewar; Atharva Manish Gumphekar; Kiran Kiran Sarjerao Patil; Jasmin Shakil Mulani; Vaibhavi Sanjay Bhosale (International Journal of Sustainable Applied Sciences, 2024)
This study investigates the influence of three Bahar treatments—Ambe Bahar (spring flowering), Mrig Bahar (monsoon flowering), and Hasta Bahar (autumn flowering)—on the extent of nematode infestation in pomegranate orchards. The research was conducted in major pomegranate-growing regions of India, where soil samples were collected from fields practicing each of the Bahar treatments. The results revealed significant differences in nematode infestation levels across the three Bahar treatments. Mrig Bahar exhibited the lowest nematode density, with an average of 80 nematodes per 100g of soil, compared to 120 in Hasta Bahar and 150 in Ambe Bahar. Additionally, Mrig Bahar treatment was associated with the highest average yield (12.8 kg per plant) and superior fruit quality (Grade A). The findings suggest that Mrig Bahar offers a more conducive environment for nematode management, likely due to its timing relative to environmental conditions that may suppress nematode activity. The results revealed significant differences in nematode infestation levels across the three Bahar treatments. Mrig Bahar exhibited the lowest nematode density, with an average of 80 nematodes per 100g of soil, compared to 120 in Hasta Bahar and 150 in Ambe Bahar. Additionally, Mrig Bahar treatment was associated with the highest average yield (12.8 kg per plant) and superior fruit quality (Grade A). The findings suggest that Mrig Bahar offers a more conducive environment for nematode management, likely due to its timing relative to environmental conditions that may suppress nematode activity. This study underscores the importance of selecting the appropriate Bahar treatment to mitigate nematode infestation and optimize pomegranate production. The insights gained from this research can guide farmers in choosing the most effective cultivation practices, ultimately contributing to sustainable pomegranate farming and improved economic outcomes. Further research is recommended to explore the underlying mechanisms that confer resistance in Mrig Bahar and to develop integrated nematode management strategies tailored to specific Bahar treatments.